Texts and Contexts— Into Pedagogy of Social Sciences in Primary Classes - Bassi, Tripti (THE PRIMARY TEACHER, 2018)
Social Sciences occupy unique significance in the disciplinary domain of school knowledge. They are integral for building understanding of social realities and meanings. In the form of Social Studies, they enrich school learning by introducing children to concepts related to the self, neighbourhood and society, among others. This paper is based on content analysis of three textbooks of Social Studies introduced by the State Council of Educational Research and Training, Delhi, in 2004, following a distinct approach by introducing children to concepts in a sequential and developmental manner through Class III textbook ‘My Delhi’ (Meri Dilli), Class IV textbook ‘Our India’ (Hamara Bharat), and ‘Our World’ (Hamari Duniya). According to the National Curriculum Framework 2005, Class III onwards Environmental Studies should be introduced for building cognitive capabilities. Discussions related to natural and social environments have to be presented to the learners in an integrated and cohesive manner. However, the successful exercise of underlining the social and cultural aspects related to the self and the world around is vividly brought through these textbooks, and offers an appreciative way by its innovative and distinct approach to situate Social Sciences within the discourse of school knowledge.